Effectiveness of an Interventional Program on Nurses Practices regarding Removing and Cleaning Burn Dead Tissue - khoder, yas (Iraqi National Journal of Nursing Specialties, 2022)
Abstract Objective(s): The study aims to measure the effectiveness of the program on removing dead tissue for burn patients by testing the nurses before the program in addition to testing them again after implementing the educational program.Methodology: The study is quantitative in nature (one experimental) and will employ pre- and post-testing techniques between October 17, 2020 and March 20, 2022. A non-probability (purposive) sample of 24 nurses working in the Azadi Teaching Hospital's Burns and Plastic Surgery Center was chosen. The experimental survey of nursing practice, a literature review, scientific records, and previous research were all taken into consideration when developing the training program and study's conclusion. The program's information and tool are reviewed by sixteen experts representing a variety of areas, and the instrument's dependability is established through test and retest. The effectiveness of the nurse education program is evaluated using 22 clinical criteria for first burn treatment. In SPSS version 22, descriptive and inferential statistics are used to analyze the data. Results: The findings show that men between the ages of 30 and 39, graduates of high school, and people with less than five years of experience made up the vast majority of the sample. The majority of the samples participated in a burn course that was conducted in Iraq. In addition to significant comparisons, there were significant differences at P 0.01 in the removal of necrotic tissue and the cleaning of burns. Conclusions: study conclude that nurses practice regarding initial burn management improved due to implementing the suggested intervention program.  Recommendations: the study recommends that providing of an educational program about removing and cleaning burn dead tissue as part of the curriculum in burns and plastic surgery center is essential.